Задачи стратегического анализа на различных стадиях развития предприятия (Путеводитель предпринимателя)
The determination of life cycle stages necessity for strategic analysis objects has been demonstrated in the article. The analysis problems for different combinations of development stages of industry, markets and organization has beenformulated. The sequence of solving these problems has been suggested in the article.